2008
DOI: 10.1016/j.brainres.2008.01.093
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine alters blood brain barrier permeability via the modulation of tight junction expression: Implication for HIV-1 neuropathogenesis in the context of drug abuse

Abstract: The pathogenesis of human immunodeficiency virus (HIV) associated encephalopathy is attributed to infiltration of the central nervous system (CNS) by HIV-1 infected mononuclear cells that transmigrate across the blood brain barrier (BBB). The endothelial tight junctions (TJ) of the blood brain barrier (BBB) play a critical role in controlling cellular traffic into the CNS. Neuropathogenesis of HIV-1 is exacerbated by drugs of abuse such as methamphetamine (Meth) which are capable of dysregulating BBB function.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
117
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(127 citation statements)
references
References 84 publications
3
117
1
1
Order By: Relevance
“…ALC Prevented the METH-Induced Loss and Redistribution of Claudin-5 METH-induced changes in claudin-5 were previously reported [3,9,10]. Here, we aimed to assess the effect of ALC 1 mM in preventing these changes.…”
Section: Alc Prevented the Meth-induced Loss Of F-actin Filaments Alimentioning
confidence: 88%
See 3 more Smart Citations
“…ALC Prevented the METH-Induced Loss and Redistribution of Claudin-5 METH-induced changes in claudin-5 were previously reported [3,9,10]. Here, we aimed to assess the effect of ALC 1 mM in preventing these changes.…”
Section: Alc Prevented the Meth-induced Loss Of F-actin Filaments Alimentioning
confidence: 88%
“…METH is increasingly recognized to impact also nonneuronal cells, such as microglia, and astrocytes and the blood-brain-barrier (BBB), causing the release of inflammatory mediators and astrogliosis [1,3,7,8]. The concept of METH-induced damage at the level of the BBB has gained relevance over the last few years, justifying the interest in understanding its consequences at the endothelium [4,9,10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Methamphetamine use has been associated with both transmission and acquisition of HIV among MSM [2,3,9,10]. Recent studies have also shown methamphetamine use to increase the rate of progression of HIV disease [11][12][13][14]. Reports of four major U.S. cities found 9.5% of MSM reported methamphatimine use within the past 6 months [15].…”
Section: Introductionmentioning
confidence: 99%